2019
DOI: 10.1016/j.ijcard.2019.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early, individualised and intensified follow-up after open heart valve surgery on unplanned cardiac hospital readmissions and all-cause mortality

Abstract: Effect of early, individualised and intensified follow-up after open heart valve surgery on unplanned cardiac hospital readmissions and all-cause mortality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…In this retrospective cohort study, 25% of all patients undergoing open‐heart valve surgery experienced unplanned, cardiac readmission within 30 days and 37% within 180 days after discharge. These numbers correspond to similar studies reporting readmission rates up to 27% within 30 days after discharge, indicating high readmission rates after open‐heart valve surgery in general 1,4,15 . Similarly, others have found readmission rates up to 43% at 180‐days after discharge and 56% within the first year 1,2,5 …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this retrospective cohort study, 25% of all patients undergoing open‐heart valve surgery experienced unplanned, cardiac readmission within 30 days and 37% within 180 days after discharge. These numbers correspond to similar studies reporting readmission rates up to 27% within 30 days after discharge, indicating high readmission rates after open‐heart valve surgery in general 1,4,15 . Similarly, others have found readmission rates up to 43% at 180‐days after discharge and 56% within the first year 1,2,5 …”
Section: Discussionsupporting
confidence: 88%
“…Prediction of readmission of any kind is difficult, involving a variety of factors, both quantifiable and nonquantifiable, including the likelihood of the patient seeking medical attention and the willingness of the admitting physician to readmit the patient to the hospital. However, in a recent prospective cohort study, conducted by the same research group as of the current paper, it has been demonstrated how it is possible to reduce readmission rates after open‐heart valve surgery by early, intensified follow‐up after discharge 15 . However, more research investigating similar interventions is needed to design the appropriate monitoring after valve surgery.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…clinical outcomes and which imposes high costs on both patients and the healthcare system 10 as reflected by long hospital stays and more readmissions. 11 In a new movement to decrease healthcare costs, much attention has been focused on the rate of readmission during the first 30 days after discharge from hospital.…”
mentioning
confidence: 99%